Harmonisasi Teknologi dan Pedagogi: Implementasi Augmented Reality Terhadap Pendidikan - Agung Puji Santoso; Umi Nur Arifah; Mirotus Sakdiah; Diana Manzil; Nila Rahmawati; M. Wahyu Putra Utama (LPPM Institut Pendidikan Nusantara Global, 2026)
The integration of Augmented Reality (AR) into the educational ecosystem has developed rapidly as an innovative solution to bridge the gap between abstract theoretical concepts and concrete visual experiences. This research aims to synthesize findings regarding the implementation of AR technology as a learning medium and its impact on the educational process. This study employs the Systematic Literature Review (SLR) method, following a systematic procedure that includes problem formulation, literature searching, study quality selection, data extraction, and data synthesis and analysis. Thirty selected literatures published between 2021 and 2026 were analyzed to evaluate technical feasibility, user response, and the pedagogical impact of AR technology. The results indicate that AR technology is consistently proven effective in visualizing abstract concepts, increasing motivation, and supporting active student engagement compared to conventional learning methods. However, a research focus disparity was identified, where literature within this period is still dominated by software development evaluation and expert validation, while empirical evidence regarding the long-term impact on knowledge retention and changes in students' cognitive behavior remains limited. Therefore, this research recommends a shift in research paradigm from mere technical validation toward more in-depth experimental studies to measure the effectiveness of AR in substantially improving the quality of the educational process.